Blood simple [videorecording (DVD)] - Coen, Joel; Getz, John, 1946-; McDormand, Frances; Hedaya, Dan (Criterion collection, 2016)
A man hires a private investigator to kill his wife, who he thinks is cheating on him, and her lover, but the investigator has a plan of his own. A bad situation suddenly gets worse.